Modification of surface layers of metal parts by pulse laser processing - M. N. Vereschagin; S. N. Tselueva; M. Yu. Tseluev (Литьë и металлургия, 2020)
One of the common technological schemes for the laser processing of metal parts is laser «glazing» of the deposited thin layer of powder on the substrate, which makes it possible to obtain microcrystalline and amorphous structures in thin surface layers of parts. Pulse melting of small volumes of metal on the surface provides homogeneous liquids (melts), which, after crystallization, can fix the structure of a liquid with unique properties.The presence of three energy input ranges for pulsed laser surface treatment (ILPO) has been established. At an average level of energy input, a process of laser surfacing of the material occurs, while a high adhesive bond between the coating and the workpiece is fixed. The deposition of an amorphized iron-based alloy coating on a metal base of St3, 45 20X13 steels begins at a laser radiation density on the treatment surface of 1800–2000 W/mm2, and alloying at 3500–4000 W/mm2. With ILPO, the laser exposure zone (ZLV) has a layered structure – the fusion zone (ZO), the heat-affected zone (HAZ), and the source material zone. To obtain an amorphous-crystalline structure of the coating, the laser pulse frequency should not exceed 3–8 Hz.